The mediating effects of personal values on the factors that influence consumer leftovers food waste - Luga, Eda; Mehmeti, Gentjan; Thoma, Ledia; Çela, Shpresa; Shehu, Erion (Edelweiss Applied Science and Technology, 2025)
The food consumption and its impact on environmental and ethical issues have attracted the attention of researchers from various disciplines. Therefore, the purpose of this study is to assess the direct and indirect influence of consumer personal values on the effect of the antecedents of food consumption causes, such as environmental attitudes, health risk concerns, and the use of a healthy diet. This paper has utilized knowledge from the theory of values, beliefs, and norms, which are considered important in the assessment of consumer behavior in food consumption. The main findings of this study suggest that personal values mediate the positive effect of consumer concerns about the environment, health risks, and healthy diets on food waste avoidance routines. This indicates that influencing individuals through education, business, and family programs can ensure positive future behavior toward consumer efforts to reduce food waste. This study aims to contribute new knowledge to support practitioners in designing and prioritizing behavioral interventions to reduce household food waste. To carry out this study, a questionnaire was conducted with 454 consumers regarding cooking or food security practices in their families. The data were collected face-to-face and processed with Structural Equation Modeling (SEM).